A Situational Analysis of Educational Supervision in the Turkish Educational System - Tuncay Yavuz Ozdemir; Ramazan Yirci (ÜNİVERSİTEPARK Limited, 2015)
The purpose of this study is to conduct a situational analysis on the educational supervisions carried out within the Turkish educational system. Content analysis was used in this study, which is one of the qualitative research methods. An interview form was prepared by the researchers in accordance with the study purpose and expert opinion sought to ensure content and face validity. Findings of the study show that; supervision is necessary for an increase in educational quality, sustainability of educational worker development, determination and elimination of possible deficiencies, to ensure not falling behind developments in the educational system, and to collaborate within the school. It has been determined that the agents who carry out the supervision should have professional competencies, should be able to enter into effective communication, should be able to spare enough time for supervision and follow the principles of equality. In addition, the importance of effective and sufficient guidance and parental participation was highlighted. In a change to the Turkish educational system in 2014, the authority and responsibility of supervision was assigned to the school principals. Because it would decrease the psychological pressure that supervision imposes on educational workers, and enable a positive atmosphere for communication over a prolonged period, this change was believed to be beneficial overall. According to another standpoint, because school principals lack professional competencies regarding educational supervision and do not follow the principles of equality, this change instead was believed to be unfavorable.